"And yet I Stond": Posture and Contemplative Theology in Julian of Norwich's Revelations of Divine Love - Ard, DeVan (Journal of medieval religious cultures, 2026)
Julian of Norwich's Revelations of Divine Loveengages extensively with the representation and experience of the human body, including the author's own experience of illness. This article argues that bodily posture helps Julian to understand the relationship between the physical body and the highly abstract, theologized body of the servant in the famous lord and servant parable, who suffers pains that bear a striking similarity to Julian's own. The article also argues that Julian's use of posture constitutes a "postural theology" traceable to works of contemplative theology from earlier in the Middle Ages (e.g., Gregory the Great) and to her contemporary Christine de Pizan.